Pronunciation Errors in Students’ Vlog Projects - Ika Fathin Resti Martanti (Universitas Muhammadiyah Kalimantan Timur, 2022)
This research explored the pronunciation errors produced by the students in their vlog projects and the linguistics factors that contributed to their errors. This study employed a descriptive qualitative method. The data were collected from the vlogs made by the students which were uploaded on Youtube channels. The participants were 30 students of the Air Transport Management study program in STTKD Yogyakarta. The data collection technique was done by observation and documentation. The data were analyzed by applying qualitative data analysis. The data were classified using the theory from Bonaventura, Herron, and Menzel (2000). The results showed that there were 67 pronunciation errors existed in the vlog projects. The mispronunciations could be categorized into three types of errors, namely: the problems of non-native sounds as many as 34%, the carry-over of pronunciation regularities from the mother tongue as many as 45%, and the over-generalization of target language (L2) regularities as many as 21%. It is expected that the findings can help students diagnose their errors and mistakes in English pronunciation and later can motivate them to improve their English proficiencies. Besides, it can help the teachers develop strategies to minimize students’ errors in pronunciation.